Penegakan Hukum terhadap Pelanggaran Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) Darurat di Kota Denpasar - Ni Made Dwi Ari Cahya Utami; I Made Minggu Widyantara; Ketut Adi Wirawan (Jurnal Konstruksi Hukum, 2022)
Since the Covid-19 pandemic that has been going on in Indonesia, the government has finally issued various policies regarding this problem, because people experience health difficulties as well as in terms of earning a living or the economy. One of the government's policies is to implement PPKM which is based on the Instruction of the Minister of Home Affairs Number 15 of 2021 concerning the Enforcement of Restrictions on Emergency Community Activities for Coronavirus Disease 2019 in the Java and Bali Regions. This study aims to determine Law Enforcement against Violations of the Enforcement of Community Restrictions (PPKM) Daryrat in Denpasar City. This study uses an empirical type. Consists of primary and secondary, with interview data collection techniques and literature study. Analyzed descriptively-qualitatively. The results showed that the Provincial Government of Bali, in this case the Governor of Bali, has issued a Circular Letter of the Governor of Bali Number 09 of 2021 concerning the Implementation of Emergency Community Activity Restrictions (PPKM) for Coronavirus Disease 2019 in the New Era of Life in the Province of Bali. The circular contains guidelines regarding the implementation of PPKM at the regional level, which later became the basis for the Task Force for the Acceleration of Handling Covid-19 in Denpasar City, namely Denpasar Mayor Regulation Number 32 of 2020 concerning Restrictions on Community Activities in Kelurahan Villages and Traditional Villages in Accelerating Corona Handling. Virus Disease 2019.